2018
DOI: 10.1111/pce.13392
|View full text |Cite
|
Sign up to set email alerts
|

Gating control and K+ uptake by the KAT1 K+ channel leaveraged through membrane anchoring of the trafficking protein SYP121

Abstract: Vesicle traffic is tightly coordinated with ion transport for plant cell expansion through physical interactions between subsets of vesicle‐trafficking (so‐called SNARE) proteins and plasma membrane Kv channels, including the archetypal inward‐rectifying K+ channel, KAT1 of Arabidopsis. Ion channels open and close rapidly over milliseconds, whereas vesicle fusion events require many seconds. Binding has been mapped to conserved motifs of both the Kv channels and the SNAREs, but knowledge of the temporal kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…S5), much as has been reported in the past (Hoshi, 1995;Gajdanowicz et al, 2009;Lefoulon et al, 2018). As before (Grefen et al, 2015;Zhang et al, 2015Zhang et al, , 2017Lefoulon et al, 2018), co-expression with SYP121 and with VAMP721 ( Fig. 5, A and B) showed opposing effects on KAT1 gating: SYP121 co-expression .…”
Section: Syp121 Coordinates With Snap33 and Vamp721 In K 1 Channel Gasupporting
confidence: 81%
See 3 more Smart Citations
“…S5), much as has been reported in the past (Hoshi, 1995;Gajdanowicz et al, 2009;Lefoulon et al, 2018). As before (Grefen et al, 2015;Zhang et al, 2015Zhang et al, , 2017Lefoulon et al, 2018), co-expression with SYP121 and with VAMP721 ( Fig. 5, A and B) showed opposing effects on KAT1 gating: SYP121 co-expression .…”
Section: Syp121 Coordinates With Snap33 and Vamp721 In K 1 Channel Gasupporting
confidence: 81%
“…KAT1 assembles as a homotetramer, but its close homolog, the so-called "silent" KC1 channel monomer, normally functions in vivo as a heterotetramer with the AKT1 K 1 channel subunit (Duby et al, 2008;Honsbein et al, 2009). Both channel assemblies show gating that is significantly altered, with opposing effects, by SYP121 and VAMP721 (Honsbein et al, 2009;Grefen et al, 2010Grefen et al, , 2015Zhang et al, 2015Zhang et al, , 2017Lefoulon et al, 2018). However, it is not known whether these characteristics are retained in combination with the cognate Qbc-SNARE SNAP33.…”
Section: Syp121 Coordinates With Snap33 and Vamp721 In K 1 Channel Gamentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies have demonstrated a direct interaction between SYP121 and another K + channel KAT1, and have shown that the addition of SYP121 could enhance the whole cell current when coexpressed with KAT1 in Xenopus oocytes . Studies with temporal kinetics of the channel gating showed that expression of SYP121 significantly alters the lifetime of KAT1 in both open and close states (Figure 1D) (Lefoulon et al 2018). These findings confirmed the unique function of SYP121 in the direct regulation of K + channel activities.…”
Section: The Roles Of Unique Snare and Escrt: Beyond Trafficking In Pmentioning
confidence: 99%